Knowledge and opinions on open access in Argentina, Mexico and Brazil - Bongiovani, Paola Carolina (2015)
The chapter surveys the knowledge, attitudes and opinions regarding OA publishing among researchers who evaluate the academic career of their peers in the area of Social Sciences in Argentina, Brazil and Mexico, in order to understand the challenges facing the OA movement in the region.